Islamic Education in Supply Chain System by Prioritizing Manners as a Success Factor of Millennial Generation on Socializing - Syamsul Huda; Muawanah Muawanah; Munifah Munifah; Muhamad Syazali; Endah Kinarya Palupi; Rofiqul Umam; Hasan Said Tortop (International Journal of Supply Chain Management, 2020)
Abstract-The progress of Science, Technology, Engineering and Mathematics (STEM) in the Era of the Industrial Revolution 4.0 requires that learning systems in schools must be developed by considering the supply chain. Since June 2006 the Tebuireng Islamic Boarding School has been developing an education system based on the supply chain strategy. In this development, the Tebuireng Islamic Boarding School begins with a religious-based education or theology that prioritizes manners in supply chain. In this case, we analyzed learning success factors based on Law Auguste Comte as the objective in this study. The study aimed to investigate the relationship between anticipation ability, supply chain, ability to accommodate and integration of education system with the mediation effect of self-organizing skills. In addition, a collaboration of 3 countries was also carried out to seek integration of schools in developed countries such as Japan and Turkey as a reinforcing factor for the success of the education system for the millennial generation in socializing. The results of the study provide very strong information and compatibility in the success of student learning, attitudes, and behavior as a millennial generation in the Industrial Revolution Era 4.0. The most dominant success factor in learning success based on the results of school integration in Japan, Turkey, and the TebuirengPesantren is the respect for others based on the formation of good characters, such as tolerance, respect, polite in speaking, and polite in acting. Besides, learning models such as Innovative learning are the most suitable models in the Industrial Revolution Era 4.0, because at this time almost all learning is based on the Internet of Things (IoT) as a very good learning media.KemajuanScience, Technology, Engineering and Mathematics (STEM) pada Era RevolusiIndustri 4.0.